The Protective Role of Hyaluronic Acid in Cr(VI)-Induced Oxidative Damage in Corneal Epithelial Cells. (27th March 2017) - Wu, Wei; Jiang, Hua; Guo, Xinnian; Wang, Yu; Ying, Shibo; Feng, Lingfang; Li, Tao; Xia, Hailing; Zhang, Yixiao; Chen, Riping; Chen, Tianhui; Lou, Jianlin
Abstract : Cr(VI) exposure could produce kinds of intermediates and reactive oxygen species, both of which were related to DNA damage. Hyaluronan (HA) has impressive biological functions and was reported to protect corneal epithelial cells against oxidative damage induced by ultraviolet B, benzalkonium chloride, and sodium lauryl sulfate. So the aim of our study was to investigate HA protection on human corneal epithelial (HCE) cells against Cr(VI)-induced toxic effects. The HCE cell lines were exposed to different concentrations of K2 Cr2 O7 (1.875, 3.75, 7.5, 15.0, and 30 μ M) or a combination of K2 Cr2 O7 and 0.2% HA and incubated with different times (15 min, 30 min, and 60 min). Our data showed that Cr(VI) exposure could cause decreased cell viability, increased DNA damage, and ROS generation to the HCE cell lines. But incubation of HA increased HCE cell survival rates and decreased DNA damage and ROS generation induced by Cr(VI) in a dose- and time-dependent manner. We report for the first time that HA can protect HCE cells against the toxicity of Cr(VI), indicating that it will be a promising therapeutic agent to corneal injuries caused by Cr(VI).